2022
DOI: 10.1136/bmjopen-2021-054682
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of serum lipid levels in patients with hypertension: a hospital-based retrospective descriptive study

Abstract: BackgroundDyslipidaemia is different among patients with hypertension in different populations. The serum lipid profiles among Hakka patients with hypertension in southern China are still unclear.Methods35 448 patients with hypertension were enrolled in this study from January 2016 to October 2020, and their serum lipids were analysed.ResultsLow high-density lipoprotein-cholesterol (HDL-C) (29.9%) accounted for the highest proportion in dyslipidaemia, followed by high triglyceride (TG) (20.7%), high total chol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 49 publications
(72 reference statements)
1
2
0
Order By: Relevance
“…Tanzania and other third world countries are undergoing epidemiological transition associated with urbanisation and sedentary lifestyle with increasing overweight/obesity, dyslipidaemia, hypertension, diabetes, CVDs and CKD 27 30 46. In this study, the prevalence of dyslipidaemia among patients with uncontrolled hypertension was 60.0%, similar to the findings from previous studies where the prevalence increased with uncontrolled hypertension and across the CKD stages from 1 to 5 50 51. The prevalence of dyslipidaemia among patients with uncontrolled hypertension and CKD is usually high 52 53.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Tanzania and other third world countries are undergoing epidemiological transition associated with urbanisation and sedentary lifestyle with increasing overweight/obesity, dyslipidaemia, hypertension, diabetes, CVDs and CKD 27 30 46. In this study, the prevalence of dyslipidaemia among patients with uncontrolled hypertension was 60.0%, similar to the findings from previous studies where the prevalence increased with uncontrolled hypertension and across the CKD stages from 1 to 5 50 51. The prevalence of dyslipidaemia among patients with uncontrolled hypertension and CKD is usually high 52 53.…”
Section: Discussionsupporting
confidence: 87%
“…27 30 46 In this study, the prevalence of dyslipidaemia among patients with uncontrolled hypertension was 60.0%, similar to the findings from previous studies where the prevalence increased with uncontrolled hypertension and across the CKD stages from 1 to 5. 50 51 The prevalence of dyslipidaemia among patients with uncontrolled hypertension and CKD is usually high. 52 53 Dyslipidaemia is associated with rapid CKD progression, and increased morbidity and mortality from CVD.…”
Section: Discussionmentioning
confidence: 99%
“…The study also reported a significant difference in LDL-C levels among individuals of different ages, with the exception of those aged 50-59 years compared to those aged <50 years, where there was no difference in the mean; however, the mean difference was statistically significant in all age groups in females and males except for those aged <50 years. High levels of HDL-C were observed in individuals aged 50-59 years, 60-69 years, 80-89 years, and ≥90 years compared to those aged <50 years, and there were statistically significant differences in HDL-C levels among various age groups when comparing females with males, and HDL-C levels among females of various ages were greater than those among males [51]. In adults living in the southeastern coastal region of China, the prevalence of dyslipidemia and the risk of CVDs were studied, and the overall prevalence of dyslipidemia was 56.8% among older adults.…”
Section: Association Of Lipid Profile Abnormalities and Cvdsmentioning
confidence: 87%
“…Patients with hypertension exhibited serum lipid levels that varied depending on age and sex, with non-elderly individuals being more prone to dyslipidemia compared to the elderly. Female patients exhibited higher TG, LDL-C, and TC levels compared to males (24).…”
Section: Introductionmentioning
confidence: 84%
“…Oxidized low-density lipoprotein (ox-LDL) is a crucial component in the impact of hyperlipidemia on vascular endothelial damage. Ox-LDL primarily induces damage and dysfunction in the endothelium, favoring the development of atherosclerosis (24,28). The process of LDL oxidation is not clearly defined.…”
Section: The Role Of Dyslipidemia In the Pathogenesis Of Hypertensionmentioning
confidence: 99%